The influence of testing algorithm for the tactics of surgical intervention in the breast cysts - Tonkoglas, A. A.; Sykal, N. A.; Sykal, I. N.; Kolesnik, V. P.; Sivozhelezov, A. V. (Journal of Education, Health and Sport, 2017)
Tonkoglas A. A., Sykal N. A., Sykal I. N., Kolesnik V. P., Sivozhelezov A. V. The influence of testing algorithm for the tactics of surgical intervention in the breast cysts. Journal of Education, Health and Sport. 2016;6(11):680-684. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.212980 http://ojs.ukw.edu.pl/index.php/johs/article/view/4089 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. The influence of testing algorithm for the tactics of surgical intervention in the breast cysts A. A. Tonkoglas, N. A. Sykal, I. N. Sykal, V. P. Kolesnik, A. V. Sivozhelezov Kharkiv National Medical University surgerydepartment №2 Abstract 112 women investigation with cystic forms of mastopathyis performed. It is revealed, that ultrasonic investigations is a highly effective method of mastopathy diagnostics. Ultrasonic diagnostic criteria at suspicion on malignizationagainst the background fibrous-cystic mastopathyare established. The differential order is definedduring pathological conditions, the diagnostic algorithm is developed. Sensitivity of ultrasonic investigation at mastopathyhas made 90,0±2,6 %. Keywords: cancer of breast, mastopathy, diagnostics, ultrasonography, mammography.